Pengaruh Kemampuan Verbal Terhadap Prestasi Belajar Matematika Siswa Kelas VIII SMP Negeri 1 Kapontori - La Eru Ugi; Askandar Askandar (Jurnal Akademik Pendidikan Matematika, 2021)
The purpose of this study was to determine the effect of verbal ability on mathematics learning achievement of class VIII students of SMP Negeri 1 Kapontori. This study used an ex-post factorial design. The population of this study were all grade VIII students of SMP Negeri 1 Kapontori in the academic year 2020/2021. The sample was students of class VIII-A 30 and VIII-B 27 who were selected using the proportional random sample technique. The research instrument was a questionnaire and student learning achievement. The results obtained are: 1) The verbal ability of the eighth grade students of SMP Negeri 1 Kapontori has excellent abilities and has high, medium and low verbal skills. The verbal ability of class VIII students of SMP Negeri 1 Kapontori is in the medium category with a percentage of 75.5% this is because verbal skills are very good.